Histochemical study of carbohydrates in clove scolex of Khawia grypi - Sindus Al-Kallak; Zuhair Rahemo (College of Education for Pure Sciences, 2006)
This projevt was undertaken to detect histovhemically the different types of carbohydrates in a recently described species of caryophyllid, Khawia grypi sp. N. using four techniques namely, periodic - Schiff reaction (PAS), Alcian blue (AB) technique (both at Ph 205 AND 1) AND Bests carmine (BC) technique. Tegument reacted intensely with (PAS), and moderately with (AB) (both Ph 2.5, and I) and negatively reactev by using (BC) . The muscle bundles were intensely reacted when using (BC) and negatively reacteve when using (AB) (Ph 2.5). The mesenchymal tissue was intensely to moderately reacted in the three techniques except (AB) (at Ph1). The excretory canals were just positively reacted except the reaction was negatively reacteve when using (AB) (Ph2.5). It has been concluded from the preset study that the Carbohydrates which were detected in the body wall contribute in protection, movement, absorption, and storage of energy, and the mesenchyma is the main site for the storage and distribution and metabolism of carbohydrates.